A????es p??blicas federais de fomento ?? leitura, ao livro e ?? biblioteca no Brasil - Mesquita, Denizete Lima de (2018)
Public actions should be acts designed and planned to resolve and / or remedy social problems related to one or more areas. Such actions are usually developed and implemented by federal, state, municipal and / or partnerships. In Brazil, such actions are planned and developed, mostly, to meet a socioeconomic demand generally instigated by society and debated by researchers and scholars. With regard to the Brazilian educational and cultural areas, there are numerous gaps arising from centuries of meager investments in the above-mentioned areas. Thus, the present research aimed to study how federal public actions to promote reading, books and libraries are being implemented and implemented in the state of Piau??. To that end, a chronological cut was made between 1990 and 2016, when there was a significant increase in investments in programs, projects and plans aimed at encouraging reading, use and access to books and libraries. Initially, we tried to present a historical retrospective on reading, books and libraries, from the earliest vestiges to the present day. In order to elaborate the theoretical framework, we used the works of scholars and researchers on the subject, like Higounet (2003); Ficher (2006); Battles (2003); Milanesi (1998); Campbell (2015); Belo (2008); Chartier (1999); Martins (2002) and others. For further immersion in the subject, there were brief conceptualizations on culture, cultural policy and cultural actions, as well as a historical overview of reading, books and libraries in Brazil and the main actions (programs, projects and policies, etc.) developed by the federal government teaching and incentive to read, use and access books and libraries. The study starts from a bibliographical and documentary research and for the apro-grounding it is necessary to carry out a field research, considering that, according to Severino (2007), in this type of research the object is analyzed in its am natural environment and the collection of data and information occur naturally in the place where they occur and without the intervention of the researcher. The study will focus on the implementation and management of federal public actions in the state of Piau??, with the main focus of the study. research the Teresina capital, since the data will be collected mostly in SEDUC/PI and SECULT/PI, since these bodies are responsible for the implementation and execution of actions at the state level. From the reading and analysis of bibliographical and documentary references, data collection and analysis, the following considerations were reached: libraries and reading rooms of elementary schools do not have conditions for use and access to books; in state schools there is access and use, but they do not have activities to promote reading. Regarding the BPs the data in the SNBP do not correspond to the reality presented by the SEBP of Piau??. In view of the above, it is concluded that there are numerous factors that corroborate so that the federal public actions in favor of the promotion of reading, books and libraries are not carried out in a satisfactory way.